Rethinking a traditional method of participation: “town-hall meetings” to support family carers of people with dementia - Wiloth, Stefanie; Kiefer, Anna; Wittek, Maren; Arroyo y Villora, Tatjana; Obermeier, Monika; Schmitt, Eric; Kruse, Andreas (Journal of Alzheimer's disease, 2022)
A growing number of people with dementia, a simultaneous decline of professional caregivers, and changing family structures clearly illustrate the societal relevance of the question of how dementia care can be arranged and delivered in the future. The demand for innovative solutions especially to support family carers requires a deeper insight into their life situation and a focused perception of their needs. This article presents the main hypothesis that specific forms of social integration and participation based on an equal dialogue between family caregivers, the public, and policymakers is needed to achieve that. Therefore, the main point here is to give family caregivers of people with dementia a voice to learn how to better support them in caring as well as self-care. A learning process triggered by a dialogue might result in a higher level of community readiness to implement new forms of support or social innovations. The hypothesis will be supported by John Dewey’s theory of political and democratic learning and the model of transformative learning according to Jack Mezirow indicating that learning particularly succeeds in interpersonal communication. In this context, the Town-Hall Meeting method and its potential to promote interpersonal communication and reflexive learning is discussed. The article addresses an important debate, namely that of how dementia care and support of family carers can succeed. It also sets the direction for future empirical research as the Town-Hall Meeting method might be applicable for gerontological action and participatory research.